Clinical Presentation of Influenza in Children 6 to 35 Months of Age: Findings From a Randomized Clinical Trial of Inactivated Quadrivalent Influenza Vaccine. Issue 8 (August 2019) - Danier, Jasur; Rivera, Luis; Claeys, Carine; Dbaibo, Ghassan; Jain, Varsha K.; Kosalaraksa, Pope; Woo, Wayne; Yanni, Emad; Zaman, Khalequ; Acosta, Beatriz; Amanullah, Arshad; Ariza, Miguel; et al.
Abstract : Background: In an exploratory analysis of an inactivated quadrivalent influenza vaccine (IIV4) trial in children 6–35 months without risk factors for influenza, we evaluated clinical presentation of influenza illness and vaccine impact on health outcomes. Methods: This phase III trial was conducted in 13 geographically diverse countries across 5 influenza seasons (2011–2014). Children were randomized 1:1 to IIV4 or control. Active surveillance was performed for influenza-like episodes (ILE); influenza was confirmed by reverse transcription polymerase chain reaction (RT-PCR). The total vaccinated cohort was evaluated (N = 12, 018). Results: 5702 children experienced ≥1 ILE; 356 (IIV4 group) and 693 (control group) children had RT-PCR-confirmed influenza. Prevalence of ILE was similar in RT-PCR-positive and RT-PCR-negative cases regardless of vaccination. Breakthrough influenza illness was attenuated in children vaccinated with IIV4; moderate-to-severe illness was 41% less likely to be reported in the IIV4 group than the control group [crude odds ratio: 0.59 (95% confidence intervals: 0.44−0.77)]. Furthermore, fever >39°C was 46% less frequent following vaccination with IIV4 than with control [crude odds ratio: 0.54 (95% confidence intervals: 0.39−0.75)] in children with breakthrough illness. Health outcome analysis showed that, each year, IIV4 would prevent 54 influenza cases per 1000 children and 19 children would need to be vaccinated to prevent 1 new influenza case. Conclusions: In addition to preventing influenza in 50% of participants, IIV4 attenuated illness severity and disease burden in children who had a breakthrough influenza episode despite vaccination. Abstract : Supplemental Digital Content is available in the text.